Effect of cement/lime additive on clogging of vacuum-drain consolidation. Issue 5 (September 2019) - Fu, Hongtao; Chai, Jinchun
Abstract: All Addressing dredged slurry with high water content has become a critical issue for sea channel dredging and maintenance. Vacuum consolidation is an effective method for improving dredged slurry. Conventionally, the effect of a cement/lime additive on the clogging of vacuum-drain consolidation has been elusive and unclear. To study the effect of vacuum consolidation for soft clayey soils with high initial water content, a set of oedometer tests and vacuum consolidation tests were conducted by adding small amounts of cement/lime. The results indicated that the structural yield stresses of soils with cement and lime were 94.29% and 48.57% higher, respectively, than those of untreated soils. The final surface settlement of lime additive at the end of the tests was 59.68 mm less than that of soil without any additives, and that of the cement additive was close to that of soil without any additives. However, the dissipation of pore water pressure with cement/lime was more than that with untreated soil. The water content was higher when using cement/lime additive, but the vane shear strengths were greater than that of untreated soil at the end of the tests. In addition, the values of k e2 / k e1 ( k e2 is a permeability at approximately 0.2 m away from the drain, and k e1 is a permeability close to the drain) above and below the drain were less than those for untreated soil. This clearly indicated that the presence of lime/cement was effective in alleviating the problem of clogging around the drain. This study could provide a good technical guideline for vacuum-drain consolidation projects combined with the use of cement/lime.